Intravenous iron in heart failure and chronic kidney disease - Patricia Carrilho (Elsevier, 2021)
Intravenous iron therapy is increasingly being used worldwide to treat anemia in chronic kidney disease and more recently iron deficiency in heart failure. Promising results were obtained in randomized clinical trials in the latter, showing symptomatic and functional capacity improvement with intravenous iron therapy. Meanwhile, confirmation of clinical benefit in hard-endpoints such as mortality and hospitalization is expected in large clinical trials that are already taking place. In chronic kidney disease, concern about iron overload is being substituted by claims of direct cardiovascular benefit of iron supplementation, as suggested by preliminary studies in heart failure.We discuss the pitfalls of present studies and gaps in knowledge, stressing the known differences between iron metabolism in heart and renal failure. Systemic and cellular iron handling and the role of hepcidin are reviewed, as well as the role of iron in atherosclerosis, especially in view of its relevance to patients undergoing dialysis. We summarize the evidence available concerning iron overload, availability and toxicity in CKD, that should be taken into account before embracing aggressive intravenous iron supplementation. Resumen: La suplementación con hierro intravenoso es cada vez más frecuente a nivel mundial en el tratamiento de la enfermedad renal crónica (ERC) y, más recientemente, se ha utilizado para tratar el déficit de hierro en la insuficiencia cardiaca (IC). En esta última, se obtuvieron resultados alentadores en estudios clínicos randomizados, demostrando una mejoría sintomática y en la capacidad funcional de la IC. Sin embargo, aún se aguarda la confirmación de beneficio clínico en los objetivos principales como mortalidad y hospitalización en los estudios clínicos amplios que actualmente están en curso.En la presente revisión se discuten las dudas que se presentan en los estudios actuales y las lagunas en el conocimiento en relación con las diferencias entre la ERC y la IC sobre el metabolismo del hierro. Se ofrece una revisión sobre el manejo celular y sistémico del hierro, así como sobre el papel de la hepcidina. Adicionalmente, se explica el papel del hierro en la ateroesclerosis y su importancia principalmente en los pacientes en diálisis. Por otra parte, en esta revisión se incluye un resumen actualizado sobre lo que existe de evidencia en relación con la sobrecarga de hierro, su disponibilidad y toxicidad en la ERC, lo cual se debe tener en cuenta antes de decidir realizar una terapia intravenosa agresiva con hierro.